The impact of technology on technical and administrative creativity - a field study in the Modern Paints Company - Shifa Balsam Hassan; Salah Abdul Qader Al Nuaimi (Iraqi Journal for Administrative Sciences, 2024)
The research aims to study the relationship between the dimensions of technology and the dimensions of both technical and administrative creativity for a sample of employees of the Modern Paints Company. The research problem is based on a lack of outlook towards the dimensions of technology and its impact on creativity. The two research hypotheses are embodied in the following: There is no relationship between the dimensions of their convergence - the degree of change in the work and the degree of difficulty of the work and each of the dimensions of administrative and technical creativity. The dimensions of technology (the degree of change in the work and the degree of difficulty of the work - do not affect each of the dimensions of administrative and technical creativity) The researchers reached a number of conclusions related to the topic and appropriate recommendations were made regarding them.